Vous êtes sur la page 1sur 7

Airline Revenue An airline company flies about 25,000 passengers from J.F.K.

NY to Canada monthly at $530 per round trip ticket. Current market research
predicts that for each $5 increase in ticket price the number of passengers will
drop by 150.With this information we can determine the equation which gives us
the number of passengers in terms of the ticket price. That formula is

P = 530 +

5x whereas P is the ticket price, 530 is the current ticket price, 5 is the $5
increase and x is the number of passengers. The equation I can find with this
information is quantity, which is

Q = 25000 - 150x where 25000

represents the normal amount of passengers when ticket price is $530 and the
quantity of passengers decreases per 150 per each dollar increase, which is
represented by x. The revenue formula then is R = P*Q which becomes R = (530
+ 5x)(25000 - 150x) which is simplified to

R = 13250000 + 45500x - 750x2.

To maximize the revenue the revenue formula must be derived, changing it into 0
= 45500 - 1500x and when we solve for x we find that x = 30.33 which means
that in order to maximize profit the airline company should increase ticket prices
by $30.33 making them $560.33.

Zip-Line Into River

Video 1 I began by timing what I could in the video provided and estimating the
angle of the zip-line on the cliff. The time the person was on the zip-line was 2.97
seconds (tzip line = 2.97 seconds) and the time the person fell from letting go of the
zip-line was 1.26 seconds (tfree fall = 1.26 seconds). The angle I estimated to be
35 ( = 35). With this information I was able to find out the acceleration rate of
the person on the zip-line and when he falls from the zip line with the equation
a = g(sin), with a being acceleration, and being g acceleration due to gravity
with is a constant 9.8 m/s2. So for the acceleration of the guy on the zip line we
would plug in a = 9.8*sin35 which gives us 5.62 m/s2 (azip line = 5.62 m/s2). As

soon as the guy lets go of the zip line the only force pulling him down is gravity,
so

afree fall = 9.8 m/s2. With this information I was now able to find the average

velocity of the guy on the zip-line and free falling with the equation vf = vo + at
where vf is final velocity, vo is initial velocity, a is acceleration and t is time. For the
velocity of the zip-line we would rewrite the equation as vzip line = vo + azip line * tzip line
which becomes vzip line = 0 + 5.62(2.97) which is vzip line = 16.69 m/s. The same is
done for the free fall velocity, and the equation is vfree fall = v0 + afree fall * tfree fall which
becomes vfree fall = 0 + 9.8(1.26) which is vfree fall = 12.35 m/s. Now that we have the
velocity we can determine how far the guy traveled on the zip-line and how far he
fell to the water. We can do this because distance equal velocity times time, so d
= vt becomes dzip line = vzip line * tzip line which is dzip line = 16.69(2.97) which equals dzip
line

= 49.57 meters. The same is done for the distance of the fall, as dfree fall = vfree fall

* tfree fall which becomes dfree fall = 12.35(1.26) which equals

dfree fall = 15.56

meters. Because I know the distance the man traveled on the zip-line and the
angle at which he descended, I can now make a right triangle to figure out how
far away from the cliff the guy landed, and how tall the cliff was. I figure out how
far away from the cliff the guy landed with the equation sin35 = x/49.57
(because sin = opposite side divided by hypotenuse and the hypotenuse is the
zip-line and opposite side the distance) and when solved x = 28.43 meters which
is how far away from the cliff he landed. With the pythagorean theorem we can
find the distance between the beginning of the zip-line and where the guy let guy
of the zip-line. so a2 + b2 = c2 becomes a2 + 28.432 = 49.572 and when solving for
a we get 40.61 meters. When we add 40.61 meters to the distance of the free
fall, 15.56 meters, we get the height of the cliff to be 56.17 meters. Using what
we got from a (the height distance between when he began the zip-line and when
he let go) and the distance from the cliff to where he landed, we can find the
slope of the zipline because m (slope) = y/x so m = 40.61/28.43 and we get the

slope to be 1.43. So the equation for the function that is the zip-line would be y =
1.43x + 56.17.

Video 2 I began by timing what I could in the video provided and estimating the
angle of the zip-line on the cliff. The time the person was on the zip-line was 3.58
seconds (tzip line = 3.58 seconds) and the time the person fell from letting go of the
zip-line was 1.33 seconds (tfree fall = 1.33 seconds). The angle I estimated to be
35 ( = 35). With this information I was able to find out the acceleration rate of
the person on the zip-line and when he falls from the zip line with the equation
a = g(sin), with a being acceleration, and being g acceleration due to gravity
with is a constant 9.8 m/s2. So for the acceleration of the guy on the zip line we
would plug in a = 9.8*sin35 which gives us 5.62 m/s2 (azip line = 5.62 m/s2). As
soon as the guy lets go of the zip line the only force pulling him down is gravity,
so

afree fall = 9.8 m/s2. With this information I was now able to find the average

velocity of the guy on the zip-line and free falling with the equation vf = vo + at
where vf is final velocity, vo is initial velocity, a is acceleration and t is time. For the
velocity of the zip-line we would rewrite the equation as vzip line = vo + azip line * tzip line
which becomes vzip line = 0 + 5.62(3.58) which is vzip line = 20.12 m/s. The same is
done for the free fall velocity, and the equation is vfree fall = v0 + afree fall * tfree fall which
becomes vfree fall = 0 + 9.8(1.33) which is vfree fall = 13.03 m/s. Now that we have the
velocity we can determine how far the guy traveled on the zip-line and how far he
fell to the water. We can do this because distance equal velocity times time, so d
= vt becomes dzip line = vzip line * tzip line which is dzip line = 20.12(3.58) which equals dzip
line

= 72.03 meters. The same is done for the distance of the fall, as dfree fall = vfree fall

* tfree fall which becomes dfree fall = 13.03(1.33) which equals

dfree fall = 17.33

meters. Because I know the distance the man traveled on the zip-line and the
angle at which he descended, I can now make a right triangle to figure out how

far away from the cliff the guy landed, and how tall the cliff was. I figure out how
far away from the cliff the guy landed with the equation sin35 = x/72.03
(because sin = opposite side divided by hypotenuse and the hypotenuse is the
zip-line and opposite side the distance) and when solved x = 41.31 meters which
is how far away from the cliff he landed. With the pythagorean theorem we can
find the distance between the beginning of the zip-line and where the guy let guy
of the zip-line. so a2 + b2 = c2 becomes a2 + 41.312 = 72.032 and when solving for
a we get 59.01 meters. When we add 59.01 meters to the distance of the free
fall, 17.33 meters, we get the height of the cliff to be 76.34 meters. Using what
we got from a (the height distance between when he began the zip-line and when
he let go) and the distance from the cliff to where he landed, we can find the
slope of the zipline because m (slope) = y/x so m = 59.01/41.31 and we get the
slope to be 1.43. So the equation for the function that is the zip-line would be y =
1.43x + 76.34

Video 3 I began by timing what I could in the video provided and estimating the
angle of the zip-line on the cliff. The time the person was on the zip-line was 1.37
seconds (tzip line = 1.37 seconds) and the time the person fell from letting go of the
zip-line was 1.34 seconds (tfree fall = 1.34 seconds). The angle I estimated to be
35 ( = 35). With this information I was able to find out the acceleration rate of
the person on the zip-line and when he falls from the zip line with the equation
a = g(sin), with a being acceleration, and being g acceleration due to gravity
with is a constant 9.8 m/s2. So for the acceleration of the guy on the zip line we
would plug in a = 9.8*sin35 which gives us 5.62 m/s2 (azip line = 5.62 m/s2). As
soon as the guy lets go of the zip line the only force pulling him down is gravity,
so

afree fall = 9.8 m/s2. With this information I was now able to find the average

velocity of the guy on the zip-line and free falling with the equation vf = vo + at

where vf is final velocity, vo is initial velocity, a is acceleration and t is time. For the
velocity of the zip-line we would rewrite the equation as vzip line = vo + azip line * tzip line
which becomes vzip line = 0 + 5.62(1.37) which is vzip line = 7.70 m/s. The same is
done for the free fall velocity, and the equation is vfree fall = v0 + afree fall * tfree fall which
becomes vfree fall = 0 + 9.8(1.34) which is vfree fall = 13.13 m/s. Now that we have the
velocity we can determine how far the guy traveled on the zip-line and how far he
fell to the water. We can do this because distance equal velocity times time, so d
= vt becomes dzip line = vzip line * tzip line which is dzip line = 7.70(1.37) which equals dzip line
= 10.55 meters. The same is done for the distance of the fall, as dfree fall = vfree fall *
tfree fall which becomes dfree fall = 13.13(1.34) which equals

dfree fall = 17.59

meters. Because I know the distance the man traveled on the zip-line and the
angle at which he descended, I can now make a right triangle to figure out how
far away from the cliff the guy landed, and how tall the cliff was. I figure out how
far away from the cliff the guy landed with the equation sin35 = x/10.55
(because sin = opposite side divided by hypotenuse and the hypotenuse is the
zip-line and opposite side the distance) and when solved x = 6.05 meters which
is how far away from the cliff he landed. With the pythagorean theorem we can
find the distance between the beginning of the zip-line and where the guy let guy
of the zip-line. so a2 + b2 = c2 becomes a2 + 6.052 = 10.552 and when solving for a
we get 8.64 meters. When we add 8.64 meters to the distance of the free fall,
17.59 meters, we get the height of the cliff to be 26.23 meters. Using what we got
from a (the height distance between when he began the zip-line and when he let
go) and the distance from the cliff to where he landed, we can find the slope of
the zipline because m (slope) = y/x so m = 8.64/6.05 and we get the slope to be
1.43. So the equation for the function that is the zip-line would be y = 1.43x +
26.23.

Video 4 I began by timing what I could in the video provided and estimating the
angle of the zip-line on the cliff. The time the person was on the zip-line was 3.30
seconds (tzip line = 3.30 seconds) and the time the person fell from letting go of the
zip-line was 1.18 seconds (tfree fall = 1.18 seconds). The angle I estimated to be
35 ( = 35). With this information I was able to find out the acceleration rate of
the person on the zip-line and when he falls from the zip line with the equation
a = g(sin), with a being acceleration, and being g acceleration due to gravity
with is a constant 9.8 m/s2. So for the acceleration of the guy on the zip line we
would plug in a = 9.8*sin35 which gives us 5.62 m/s2 (azip line = 5.62 m/s2). As
soon as the guy lets go of the zip line the only force pulling him down is gravity,
so

afree fall = 9.8 m/s2. With this information I was now able to find the average

velocity of the guy on the zip-line and free falling with the equation vf = vo + at
where vf is final velocity, vo is initial velocity, a is acceleration and t is time. For the
velocity of the zip-line we would rewrite the equation as vzip line = vo + azip line * tzip line
which becomes vzip line = 0 + 5.62(3.30) which is vzip line = 18.55 m/s. The same is
done for the free fall velocity, and the equation is vfree fall = v0 + afree fall * tfree fall which
becomes vfree fall = 0 + 9.8(1.18) which is vfree fall = 11.56 m/s. Now that we have the
velocity we can determine how far the guy traveled on the zip-line and how far he
fell to the water. We can do this because distance equal velocity times time, so d
= vt becomes dzip line = vzip line * tzip line which is dzip line = 18.55(3.30) which equals dzip
line

= 61.22 meters. The same is done for the distance of the fall, as dfree fall = vfree fall

* tfree fall which becomes dfree fall = 11.56(1.18) which equals

dfree fall = 13.64

meters. Because I know the distance the man traveled on the zip-line and the
angle at which he descended, I can now make a right triangle to figure out how
far away from the cliff the guy landed, and how tall the cliff was. I figure out how
far away from the cliff the guy landed with the equation sin35 = x/61.22
(because sin = opposite side divided by hypotenuse and the hypotenuse is the

zip-line and opposite side the distance) and when solved x = 35.11 meters which
is how far away from the cliff he landed. With the pythagorean theorem we can
find the distance between the beginning of the zip-line and where the guy let guy
of the zip-line. so a2 + b2 = c2 becomes a2 + 35.112 = 61.222 and when solving for
a we get 50.15 meters. When we add 50.15 meters to the distance of the free
fall, 13.64 meters, we get the height of the cliff to be 63.79 meters. Using what
we got from a (the height distance between when he began the zip-line and when
he let go) and the distance from the cliff to where he landed, we can find the
slope of the zipline because m (slope) = y/x so m = 50.15/35.11 and we get the
slope to be 1.42. So the equation for the function that is the zip-line would be y =
1.42x + 63.79.